Clinical Practice Guidelines for cranioencephalic trauma. - Florencio Pons Moscoso; José Ramón Tejera del Valle; Jorge Luis Ulloa Capestany (Medisur)
Clinical Practice Guidelines for cranioencephalic trauma. It has been defined as the lesion received in the cranium, its covers and the encephalic content as a result of the action of external forces. This document includes a review of the classification, clinical presentation and methods used in the diagnosis and main treatment alternatives, stressing the neuro-monitoring. It includes assessment guidelines focused on the most important aspects to be accomplished.